2017
DOI: 10.1101/190165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between alcohol consumption and Alzheimer’s disease: A Mendelian randomization Study

Abstract: Observational studies have suggested that a U-shaped relationship exists between alcohol consumption and Alzheimer's disease, with light-moderate drinkers at lower risk of developing Alzheimer's disease. A two-sample Mendelian randomization approach was used to examine whether alcohol consumption causally effects the risk of developing Alzheimer's disease. We used summary level genome-wide association data for alcohol consumption from the UK biobank, alcohol dependence from the Netherlands Twin Register (NTR) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Contradicting to the previous MR study (13), our g-formula results supported a causal association between AUD and dementia. This inconsistency may relate to the different definitions of AUDwe used the formal medical diagnosis from the hospital records, whereas in the MR study AUD was assessed using the Alcohol Use Disorder Identification Test.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Contradicting to the previous MR study (13), our g-formula results supported a causal association between AUD and dementia. This inconsistency may relate to the different definitions of AUDwe used the formal medical diagnosis from the hospital records, whereas in the MR study AUD was assessed using the Alcohol Use Disorder Identification Test.…”
Section: Discussionsupporting
confidence: 72%
“…On the contrary, a meta-analysis of 15 prospective cohort studies with 2-8 years of follow-up (10) and an overview of 3 systematic reviews (11) both reported no association between heavy drinking and dementia. A recent Mendelian randomization (MR) study, which is not influenced by confounding and overcomes the main bias in observational epidemiology by design (12), also showed no causal association between AUD and dementia (13). This MR study nevertheless may suffer from the violation of the exclusion restriction assumption that threats the validity of the results (14,15).…”
mentioning
confidence: 93%
“…39 A two-sample Mendelian randomization study found no evidence of a causal relationship between alcohol consumption and late-onset Alzheimer's disease; they did, however, find evidence of an association between alcohol consumption and earlier Alzheimer's age of onset. 14 A polygenic risk score based two-sample Mendelian randomization analysis of many putative modifiable Alzheimer's disease risk factors and Alzheimer's disease phenotypes found no association between alcohol consumption and Alzheimer's disease. 15 Generally consistent with these findings, our Mendelian randomization analyses were also predominantly null.…”
Section: Discussionmentioning
confidence: 99%
“…10 Prior Mendelian randomization investigations have largely found null associations between alcohol use and cognitive impairment or dementia. [11][12][13][14][15] Several of those studies only assessed cognitive impairment and relied on individual single nucleotide polymorphisms (SNPs) in the alcohol metabolism genes ALDH2 and ADH1B as genetic instruments. [11][12][13] Only one such study of 235 rural Chinese individuals found an increased risk of cognitive impairment with increased alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation